1996
DOI: 10.1038/nsb1096-874
|View full text |Cite
|
Sign up to set email alerts
|

Different folding transition states may result in the same native structure

Abstract: The crystal structures of two circular permutants of the alpha-spectrin SH3 domain with new termini within the RT loop (S19-P20s) and the distal loop (N47-D48s) have been determined at 2.02 and 1.77 A resolution respectively. Both fold into the same three-dimensional structure as the wild-type SH3 domain except for the engineered loop that fuses the wild-type termini. The cleaved RT loop in S19-P20s loses nine conserved hydrogen bonds through local hydrogen bond unzipping; no hydrogen bond unzipping occurs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
199
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(228 citation statements)
references
References 29 publications
26
199
3
Order By: Relevance
“…Moreover, the folding mechanisms of globular proteins are generally robust; only a drastic change in the energetic balance, such as by circular permutation, can in some cases shift the folding nucleus from one part of the structure to another (27)(28)(29)(30). By contrast, the experimental results for myotrophin presented here and for the 7-ANK protein Gankyrin (R. D. Hutton, A.R.L., and L.S.I., unpublished results) and the 12-ANK protein D34 (N. D. Werbeck and L.S.I., unpublished results) reveal parallel folding routes of similar energy, and simulations carried out on a number of ANK proteins also predict pathway heterogeneity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the folding mechanisms of globular proteins are generally robust; only a drastic change in the energetic balance, such as by circular permutation, can in some cases shift the folding nucleus from one part of the structure to another (27)(28)(29)(30). By contrast, the experimental results for myotrophin presented here and for the 7-ANK protein Gankyrin (R. D. Hutton, A.R.L., and L.S.I., unpublished results) and the 12-ANK protein D34 (N. D. Werbeck and L.S.I., unpublished results) reveal parallel folding routes of similar energy, and simulations carried out on a number of ANK proteins also predict pathway heterogeneity (26).…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing possibility is that folding follows a trajectory of the lowest successive loop-entropy cost (8,9). To directly test this idea we have analyzed the folding behavior of four S6 variants in which the loop-entropy cost of forming pairwise contacts has been systematically altered through circular permutation (10)(11)(12). The results show that the -value distribution defining the S6 nucleus is plastic and responds to circular permutation in a systematic manner.…”
Section: Circular Permutation ͉ -Values ͉ Transition Statementioning
confidence: 99%
“…3 and Table 4, which is published as supporting information on the PNAS web site). Evidence that the coupling between -values and loop entropy is universal is provided by an earlier analysis of circular permutants of the ␣-spectrin Src homology 3 domain (10,41) where the application of Eq. 3 to the literature data yields R ϭ 0.76 (Table 4 and Table 5, which is published as supporting information on the PNAS web site).…”
Section: Malleable Contact Recruitment Indicates Broad Folding Progrementioning
confidence: 99%
“…It may be thought of as joining the ends of a protein and then opening the chain elsewhere. These experiments have shown that it is possible in some cases to permute the termini of a protein and still allow folding into the native conformation (1,2), thus providing valuable information on protein folding. In practice the conceptual "circular proteins" intrinsic to the design of circular permutants are never actually synthesized but are theoretical intermediates.…”
mentioning
confidence: 99%